Application Drama Technique in Developing Speaking of the Eleventh Grade Students of Man Majene - Abdul Rahman R (Universitas Muhammadiyah Enrekang, 2019)
This research aims to proof whether the application of drama technique is able to develop students’ speaking skill.The design of this study is experimental design. There were two groups: experimental and control group. The research was conducted at Madrasah Aliah Negeri Majene, and took 40 students as samples. The data were collected by using the pre-test, the treatment, and the post-test. The speaking test administered to the students of experimental and control class. The scores were assessed by three assessors. The data were analyzed and interpreted by using Pearson Product Moment assisted by SPSS 20 (Statistical Package for Service Solution) software program. The result of the research reveals that application of drama technique can be proven to develop students’ speaking skill and the application of drama technique develop students’ speaking skill. The result of the students’ speaking score development from pre-test to post test demonstrates a significant difference. The researcher found that sig.(2 tailed) is 0.000 which is lower than 0.05. The outcome of the students’ speaking development comparison between experimental and control group is 0.025. It means that the development is significant. The application of drama technique developed and improve students’ speaking skill. The finding signifies that application of drama technique is responded positively by the experimental class.